Kesulitan siswa kelas viii dalam menyelesaikan soal cerita spldv dengan menggunakan langkah polya di desa cihikeu - Siti Sanidah; Tina Sri Sumartini (Institut Pendidikan Indonesia, 2022)
The difficulty is a person's lack of ability to solve a problem, for example, difficulty learning in solving story problems, giving math problems in the form of story problems to students intended to show the interconnectedness of problem-solving in everyday life, seeing the many difficulties experienced by students in solving problems. About the story, then there needs to be an analysis of the difficulty of students in solving the story problem. The purpose of this study is to find out the difficulties of class VIII students in solving SPLDV story problems in Cihikeu Village and to find out the factors that cause students to have difficulty in solving SPLDV story problems. The method in this study uses qualitative research methods, while the techniques selected are based on purposive sampling techniques for as many as 3 students. Participants in this study were students of class VIII of State Junior High School 4 Bungbulang. The techniques for data in this study are tests, interviews, and questionnaires. The results of this study showed that students had difficulty in determining the methods used and students had difficulty in proving back the results of the answers, while the causative factors were student's less understanding of concepts, students were less careful in reading the problem, and students' efforts in correcting the story question were still lacking.Kesulitan merupakan kurangnya kemampuan seseorang dalam menyelesaikan suatu masalah, contohnya yaitu kesulitan belajar dalam menyelesaikan soal cerita. Pemberian soal matematika dalam bentuk soal cerita kepada siswa dimaksudkan untuk menunjukkan keterkaitan pemecahan masalah dalam kehidupan sehari-hari, melihat masih banyaknya kesulitan yang dialami siswa dalam menyelesaikan soal cerita, maka perlu adanya analisis kesulitan siswa dalam menyelesaikan soal cerita. Adapun tujuan penelitian ini untuk mengetahui kesulitan siswa kelas VIII dalam menyelesaikan soal cerita SPLDV di Desa Cihikeu dan untuk mengetahui faktor penyebab siswa mengalami kesulitan dalam menyelesaikan soal cerita SPLDV. Metode pada penelitian ini menggunakan metode penelitian kualitatif, sedangkan teknik yang dipilih berdasarkan teknik purposive sampling sebanyak 3 siswa. Partisipan dalam penelitian ini adalah siswa kelas VIII SMP Negeri 4 Bungbulang. Adapun teknik pengumulan data dalam penelitian ini adalah tes, wawancara dan angket. Hasil penelitian ini menunjukkan bahwa siswa mengalami kesulitan dalam menentukan metode yang digunakan dan siswa mengalami kesulitan dalam membuktikan kembali hasil jawaban, adapun faktor penyebabnya yaitu siswa kurang memahami konsep, siswa kurang teliti dalam membaca soal, serta usaha siswa dalam menyelesaikan soal cerita masih kurang.